Micro-Short Audiovisual Forms and Their Narrative Structures - Sołodki, Paweł (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
This paper introduces micro-short audiovisual forms—very brief videos ranging from a few seconds to several minutes, commonly distributed via TikTok, Instagram or other social media. These forms are defined not only by duration but by distinct formal and narrative qualities shaped by mobile viewing habits and platform algorithms. Integrating concepts from film and media studies, the analysis draws on classical narratology (e.g., plot, character, presented world) and postclassical approaches, including cognitive and transmedial narratology. A five-part typology is proposed: Nomads (standalone units), Chains (linear sequences), Mosaics (nonlinear thematic clusters), Excerpts (remixes), and Satellites (paratextual extensions). Micro-shorts are presented as narratively connected elements within broader media ecosystems, redefining modes of storytelling and engagement in the digital economy of attention.